Functional analysis of seven regulators of G protein signaling (RGSs) in the nematode-trapping fungus Arthrobotrys oligospora. Issue 1 (1st January 2021) - Ma, Ni; Zhao, Yining; Wang, Yunchuan; Yang, Le; Li, Dongni; Yang, Jiangliu; Jiang, Kexin; Zhang, Ke-Qin; Yang, Jinkui
Abstract: Regulators of G protein signaling (RGSs) are proteins that negatively regulate G protein signal transduction. In this study, seven putative RGSs were characterized in the nematode-trapping (NT) fungus, Arthrobotrys oligospora . Deleting Rgs genes significantly increased intracellular cAMP levels, and caused defects in mycelia growth, stress resistance, conidiation, trap formation, and nematocidal activity. In particular, the Δ AoFlbA mutant was unable to produce conidia and traps. Transcriptomic analysis showed that amino acid metabolic and biosynthetic processes were significantly enriched in the Δ AoFlbA mutant compared to WT. Interestingly, Gas1 family genes are significantly expanded in A. oligospora and other NT fungi that produce adhesive traps, and are differentially expressed during trap formation in A. oligospora . Disruption of two Gas1 genes resulted in defective conidiation, trap formation, and pathogenicity. Our results indicate that RGSs play pleiotropic roles in regulating A. oligospora mycelial growth, development, and pathogenicity. Further, AoFlbA is a prominent member and required for conidiation and trap formation, possibly by regulating amino acid metabolism and biosynthesis. Our results provide a basis for elucidating the signaling mechanism of vegetative growth, lifestyle transition, and pathogenicity in NT fungi.